Maternal thyroid peroxidase antibody positivity and its association with incidence of low birth weight in infants - Chen, Liangmiao; Lin, Dini; Lin, Zhenzhen; Ye, Enling; Sun, Mengli; Lu, Xuemian (Frontiers in Endocrinology, 2023)
Background: Autoimmune thyroid disease is a prevalent condition affecting women of reproductive age, leading to thyroid dysfunction and impacting pregnancy outcomes. While the critical role of thyroid hormone in pregnancy outcomes is well-established, the potential association between positive anti-thyroid peroxidase antibodies (TPOAb) and adverse pregnancy outcomes in pregnant women with normal thyroid function remains unclear. Objective: This study aims to investigate the relationship between maternal TPOAb positivity and adverse pregnancy outcomes with normal thyroid function. Methods: We collected baseline information from pregnant women who visited our hospital between February 2009 and June 2012. Blood samples were taken to measure thyroid stimulating hormone (TSH), free thyroxine (FT4), TPOAb, and anti-thyroglobulin antibodies (TGAb). The incidence of adverse pregnancy outcomes was compared between TPOAb-positive and TPOAb-negative groups among participants with normal thyroid function. Results: A total of 7,046 pregnant women with normal thyroid function were included, comprising 6,700 with negative TPOAb and 346 with positive TPOAb. The TPOAb-positive group exhibited a higher age (26.0 vs. 27.0 years, p = 0.02) and greater serum TSH levels (1.72 vs. 1.94 mIU/L, p = 0.029), while the gestational week of blood collection was lower (31.9 vs. 26.5 weeks, p = 0.001). Univariate analysis revealed a higher incidence of low birth weight (LBW) in offspring of TPOAb-positive women compared to the TPOAb-negative group (3.5% vs. 1.9%, p = 0.035). After adjusting for confounding factors such as age, gestational week of blood collection, menstrual history, education level, gestational diabetes, gestational hypertension, TGAb, TSH, and FT4, TPOAb positivity emerged as an independent risk factor for LBW infants (OR: 2.317, 95% CI: 1.057–5.076, p = 0.036), while other adverse pregnancy outcomes did not show a significant correlation with TPOAb positivity. Conclusion: Our findings suggest that TPOAb-positive pregnant women with normal thyroid function are more likely to deliver LBW infants. Regular monitoring of TPOAb-positive pregnancies and timely interventions throughout all stages of pregnancy are crucial.